2022
DOI: 10.3389/fonc.2022.1025291
|View full text |Cite
|
Sign up to set email alerts
|

PABPC1——mRNA stability, protein translation and tumorigenesis

Abstract: Mammalian poly A-binding proteins (PABPs) are highly conserved multifunctional RNA-binding proteins primarily involved in the regulation of mRNA translation and stability, of which PABPC1 is considered a central regulator of cytoplasmic mRNA homing and is involved in a wide range of physiological and pathological processes by regulating almost every aspect of RNA metabolism. Alterations in its expression and function disrupt intra-tissue homeostasis and contribute to the development of various tumors. There is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 196 publications
0
9
0
Order By: Relevance
“…Recently, Gilbertson et al showed that in mammalian cells, the poly(A)-binding protein cytoplasmic 1 (PABPC1) plays a critical role in this process [41]. PABPC1 is an RBP that binds directly to the poly(A) tail of the pre-mRNA in the nucleus and is released in the cytoplasm after mRNA is degraded, functioning in mRNA translation and degradation [5658]. Researchers found that it also interferes with the formation of PIC in the nucleus [41].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Gilbertson et al showed that in mammalian cells, the poly(A)-binding protein cytoplasmic 1 (PABPC1) plays a critical role in this process [41]. PABPC1 is an RBP that binds directly to the poly(A) tail of the pre-mRNA in the nucleus and is released in the cytoplasm after mRNA is degraded, functioning in mRNA translation and degradation [5658]. Researchers found that it also interferes with the formation of PIC in the nucleus [41].…”
Section: Resultsmentioning
confidence: 99%
“…As its name suggests, RBP is a kind of protein that binds with RNA. Having a variety of regulatory, structural, and catalytic roles, functional RNA interacts with proteins to conduct functions in the cell, such as processing, transport, translation, RNA stabilization, modification, and localization (Hashimoto & Kishimoto, 2022; Qi et al, 2022; Smith & Costa, 2022). Examples supporting these abound.…”
Section: Rna‐binding Protein (Rbp)mentioning
confidence: 99%
“…The numerous functions of PABPC are attributed to its ability to interact with not only mRNAs but also various other proteins to form messenger ribonucleoprotein (mRNP) complexes [2]. PABPC's conserved structure consists of three regions: i) four RNA recognition motif (RRM) domains, two of which (RRM1 and RRM2) bind 12 adenosines with high affinity [3,4], while the protein overall covers 27 adenosines [5], ii) a proline-rich (P) linker domain, and iii) a C-terminal mademoiselle (MLLE) domain that interacts with other proteins via their PABP-interacting motif 2 (PAM2) [2,3,6]. Mammals have multiple isoforms of PABPCs, of which the most ubiquitous isoform as well as the most studied is PABPC1, whereas the yeast Saccharomyces cerevisiae has only one PABPC, Pab1 [2,3,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Current elaborations of this model postulate that mRNAs could be circularized by a chain of interactions between poly(A)-associated PABPC and 5' end-localized initiation factors, giving rise to a poly(A) tail-PABPC-eIF4G-eIF4E-5'cap network [2,[26][27][28][29][30]. eIF4G has been shown to interact with PABPC's RRM2 domain [26,[31][32][33], and disrupting this interaction reduced translation [6,29,34]. Thus, PABPC can stabilize the cap-binding complex and aid the recruitment of the 43S preinitiation complex to the mRNA [2,3,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation